Sex differences in the inflammatory response and inflammation-induced vascular dysfunction. (23rd February 2017) - Rathod, Krishnaraj; Kapil, Vikas; Velmurugan, Shanti; Khambata, Rayomand; Siddique, Umme; Khan, Saima; Gee, Lorna; Bansal, Jaspal; Pitrola, Kavi; Shaw, Christopher; D'Acquisto, Fulvio; Colas, Romain; et al.
Abstract: Background: Premenopausal women have a lower incidence of cardiovascular disease, although the exact mechanism underlying this protection is unclear. Both systemic and localised inflammation have a crucial role in the progression of cardiovascular disease, and much preclinical and observational data in human beings suggest that differences in inflammation between the sexes exist. We investigated whether inflammation, and which components of the inflammatory response, might be altered in women compared with men. Methods: We performed two clinical studies with 24 and 32 healthy volunteers. In 12 men and 12 women (mean age 26·0 years [SD 5·7] and 24·7 [6·8], respectively), we assessed systemic inflammatory markers and vascular function using brachial artery flow-mediated dilation (FMD) determined with ultrasound. Responses were assessed before administration of typhoid vaccine and then at 8 h and 32 h afterwards. In another study, in 16 male and 16 female volunteers (mean age 27·4 years [SD 1·1] and 26·8 [1·1], respectively), inflammatory exudate and cellular recruitment were measured at 24 h (acute) and 72 h (resolution) in skin blisters induced with cantharidin. Ethics approval was given by NRES: City Road and Hampstead Ethics Committee (11/LO/2038) for both studies. Both studies are registered withClinicalTrials.gov, numberNCT01582321 . Findings: Typhoid vaccine caused a mild systemic inflammation, which was associated with a trend to decreased FMD in men and an increased response in women compared with baseline (p=0·006). By 24 h cantharidin induced a fluid-filled blister of a similar volume in both sexes; however, after 72 h blisters had resolved only in women (p=0·003). At 24 h there was a significant reduction in both monocyte (p=0·003) and lymphocyte count (p=0·011) in blisters in women compared with those in men. A generalised reduction in the activation state of all major leucocytes including neutrophils was evident in women. These differences in cell recruitment and activation were associated with higher proresolving mediators, including the D-resolvins, and a reduction in concentrations of the neutrophil chemoattractant leukotriene B4. Interpretation: Our findings suggest that female sex protects against endothelial dysfunction induced by systemic inflammation. This effect is probably due to a rapid resolution of inflammation in women specifically targeting the neutrophil through elevation of the D-resolvin pathway. Funding: KR receives doctoral research fellowship funding from the National Institute for Health Research. JD receives funding from the European Research Council under the European Union's Horizon 2020 research and innovation programme (grant agreement 677542), and is also supported by a Sir Henry Dale Fellowship jointly funded by the Wellcome Trust and the Royal Society (grant 107613/Z/15/Z).